2016
DOI: 10.1108/jmd-02-2015-0017
|View full text |Cite
|
Sign up to set email alerts
|

The “Dean’s Squeeze” revisited: a contextual approach

Abstract: Purpose -To develop a conceptual framework for identifying the primary tensions that business school deans encounter when moving between different university contexts. Design/methodology/approach -The paper is part of a larger research project on the development of business schools. This conceptual paper builds on our studies and personal experiences of business schools and their management in a number of different countries, primarily in Europe, North America, Asia, and the Middle East. Findings -The present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
(43 reference statements)
1
5
0
Order By: Relevance
“…For the competitive loop to go through a full cycle, third-party initiatives and incentives need to be responded to by HEIs' strategic management. Our study, as well as previous studies, has indicated that business schools are inherently sensitive to all kinds of endogenous and exogenous "nudges" of competition that can emerge from individuals (e.g., competitive deans; Alajoutsijärvi & Kettunen 2016;Lejeune & Vas, 2014;Parker, 2018), individual departments, or changes in resource allocation. There are at least two obvious reasons for this sensitivity to competitive nudges.…”
Section: Early Institutionalization Of Competitionsupporting
confidence: 61%
“…For the competitive loop to go through a full cycle, third-party initiatives and incentives need to be responded to by HEIs' strategic management. Our study, as well as previous studies, has indicated that business schools are inherently sensitive to all kinds of endogenous and exogenous "nudges" of competition that can emerge from individuals (e.g., competitive deans; Alajoutsijärvi & Kettunen 2016;Lejeune & Vas, 2014;Parker, 2018), individual departments, or changes in resource allocation. There are at least two obvious reasons for this sensitivity to competitive nudges.…”
Section: Early Institutionalization Of Competitionsupporting
confidence: 61%
“…Still, we find it more likely that the umbrella protector positioning is a way for middle managers to handle the complicated middle-levelness in which the they are in crossfire (Alajoutsijärvi and Kettunen, 2016;Gallos, 2002;Sims, 2003). To navigate this complicated middle, we suggest they need a combination of stories and acts to organise meaning and direction for their interpretations and enactments of identity and role.…”
Section: Discussionmentioning
confidence: 93%
“…The context of HE is often described as particularly complex in terms of structure , as it has to address different markets and regulations and employ staff with short- and long-term contracts, and culture characterized by a variety of academic and corporate-informed cultures of performance, norms and values (Alajoutsijärvi and Kettunen, 2016; Bolden et al, 2009; Middlehurst et al, 2009). Intensified managerialism (Alvesson and Spicer, 2016; Keenoy, 2005; Parker and Jary, 1995; Prichard and Willmott, 1997) has led to colliding pressures and tensions for academic leaders who are caught in between opposing expectations, values and worldviews (Alajoutsijärvi and Kettunen, 2016; Gallos, 2002; Kallio et al, 2016).…”
Section: A Brief Theoretical Overview Of Academic Leadership and Middmentioning
confidence: 99%
“…The success of any accreditation endeavor is highly dependent on the business school faculty's knowledge and engagement in the project (AACSB, 2020), as Nordic accreditation project managers cannot "force" the faculty members of their institutions to educate themselves or participate in the project. Instead, they need to use other, more subtle and dialogic means to interact with the various disciplines and to overcome their longstanding and often political grievances to obtain collaboration and coherence (Alvesson & Spicer, 2016;Alajoutsijärvi & Kettunen, 2016;Huzzard, Benner & Kärreman, 2017). Therefore, the way in which projects teams use boundary objects during the one-off process of accreditation becomes pertinent.…”
Section: Boundary Object Use and The Social Stratum Of Business Schoolsmentioning
confidence: 99%